Evaluating ground glass opacities (GGO) in the COVID-19 era. Do autoantibodies help? - Pejic, Nina; Stojkovic Lalosevic, Milica; Stulic, Milos; Culafic, Milica; Culafic, Djordje (The Journal of Infection in Developing Countries, 2022)
Introduction: COVID-19 is an infectious disease, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and there have been outbreaks worldwide. The presentation may include unspecific and mild symptoms, myalgia, headaches, high fever, dry cough, severe dyspnea and acute respiratory distress syndrome (ARDS). Case study: We present a rare case of microscopic polyangiitis (MPA) with interstitial lung disease and without renal involvement misdiagnosed as COVID-19. Conclusions: Differential diagnosis of COVID-19 is extremely important, and must be correctly identified in order to proceed with correct treatment.